Reduction of cardiac iron overload by optimising iron chelation therapy in transfusion dependent thalassaemia using cardiac T2* MRI: a quality improvement project from Pakistan. Issue 11 (29th September 2020) - Hussain, Shabneez; Hoodbhoy, Zahra; Ali, Fatima; Hasan, Erum; Alvi, Najveen; Hussain, Aijaz; Ishrat, Khajista; Ur Rahman, Zia; Qamruddin, Azizuddin; Parvin, Azra; Hasan, Babar S
Abstract : Objectives: Cardiac T2* MRI (T2*CMR), for accurate estimation of myocardial siderosis, was introduced as part of a QI collaborative to optimise chelation therapy in order to improve cardiac morbidity in transfusion dependent thalassaemia (TDT) patients. We report the impact of this QI initiative from two thalassaemia centres from this collaborative. Design and setting: A key driver based quality initiative was implemented to improve chelation in TDT patients registered at these two centres in Karachi, Pakistan. Protocol optimisation and compliance to treatment through training, communication and feedback were used as the drivers for QI intervention. Preintervention variables (demographics, chelation history, T2*CMR, echocardiography and holters) were collected from January 2015 to December 2016) and compared with variables in the post implementation phase (January to December 2019). A standardised adverse event severity for chelators and its management was devised for safe drug therapy as well as ensuring compliance to the regimen. Preintervention and postintervention variables were compared using non-parametric test. P value<0.05 was statistically significant. Results: 100 patients with TDT, median age 17 (9–34) years, were included. An increase or stabilisation of T2*CMR was documented in 82% patients in the postintervention phase especially in patients with severe myocardial iron overload (5.5 vs 5.3 ms, p <0.01). Significantly fewer patients had abnormal echocardiographic findings (3.5% vs 26%, p <0.05) in the postintervention versus preintervention period. Conclusion: This QI initiative improved the chelation therapy leading to improved cardiac status in TDT patients at the participating centres. Abstract : This is a novel attempt to use improvement methodology in Pakistan to improve compliance with standards for managing iron overload in children with transfusion dependent thalasaemia. The lessons whilst specific to this disease show what is achievable if this methodology is applied rigorously.